Pengaruh Kredibilitas Influencer Terhadap Minat Beli Konsumen Pada Produk Makanan - Lumbantoruan, Astrina; Marwansyah, Marwansyah (Jurnal Riset Bisnis dan Investasi, 2023)
Purchasing activities that have switched from offline transactions to online have advantages and disadvantages. From the seller's and buyer's point of view, online transactions provide a number of benefits, including saving time, effort and costs. On the other hand, the main drawback of buying online is the difficulty of consumers to see the physical goods. To overcome this weakness, consumers seek reviews from other consumers, including influencers. In this context, influencer credibility plays an important role. This study aims to examine the effect of influencer credibility on consumer buying intention. This study uses a quantitative approach with an explanatory survey to 181 respondents. Data were analyzed using descriptive statistics and linear regression analysis. This study proves that influencer credibility has an effect on consumer buying intention. Credibility comes from from expertise and experience as well as the ability of influencers to provide product reviews.